Mapping the New Testament: early Christian writings as a witness for Jewish biblical exegesis - Ruzer, Sergʹ (Jewish and Christian perspectives series, 2007)
Preliminary material /S. Ruzer -- Introduction - The New Testament as witness for early jewish exegesis /S. Ruzer -- Chapter One. Antitheses in Matthew 5: Midrashic aspects of exegetical techniques /S. Ruzer -- Chapter Two. From \'love your neighbor\' to \'love your enemy\' /S. Ruzer -- Chapter Three. The double love precept: Between Pharisees, Jesus and Qumran covenanters /S. Ruzer -- Chapter Four. Who was unhappy with the Davidic Messiah? /S. Ruzer -- Chapter Five. Negotiating the proper attitude to marriage and divorce /S. Ruzer -- Chapter Six. The seat of sin and the limbs of Torah /S. Ruzer -- Chapter Seven. Crucifixion: The search for a meaning vis-à-vis biblical prophecy. From Luke to Acts /S. Ruzer -- Chapter Eight. The new covenant, the reinterpretation of scripture and collective messiahship /S. Ruzer -- Conclusion and perspectives /S. Ruzer -- Index of ancient sources /S. Ruzer.